Root Cause Localization in Large Scale Systems - Kiciman, Emre; Subramanian, Lakshminarayanan (Proceedings of the First Workshop on Hot Topics in System Dependability (HotDep), 2005)
Root cause localization, the process of identifying the source of problems in a system using purely external observations, is a significant challenge in many large-scale systems. In this paper, we propose an abstract model that captures the common issues underlying root cause localization and hence provides the ability to leverage solutions across different systems.